Computed tomography-guided cutting needle biopsy for lung nodules: A comparative study between low-dose and standard dose protocols. Issue 3 (22nd January 2021) - Zhang, Hui-Mei; Huo, Xiao-Bing; Wang, Hua-Long; Zhang, Xiao; Fu, Yu-Fei
Abstract : Abstract: We aim to compare the diagnostic accuracy, safety, and radiation exposure between low-dose and standard-dose computed tomography (CT)-guided cutting needle biopsy (CNB) for lung nodules. From January 2016 to August 2017, all consecutive patients admitted with lung nodule underwent low-dose or standard-dose CT-guided CNB procedure in our center. Diagnostic accuracy and radiation dose were compared. A total of 67 and 69 patients who underwent low-dose and standard-dose CT-guided CNB procedure were included in this study. Each patient underwent CT-guided CNB for 1 nodule. The technical success rates were 100% in both groups. The sensitivity, specificity, and overall diagnostic accuracy were 97.7%, 100%, and 98.5% for low-dose group and 91.5%, 100%, and 94.2% for standard-dose group. There was no significant difference in diagnostic accuracy ( P = .380) between 2 groups. Pneumothorax was found in 8 and 15 patients in the low-dose and standard-dose groups, respectively (11.9% vs 21.7%, P = .127). Hemoptysis was found in 10 and 10 patients in the low-dose and standard-dose groups, respectively (14.9% vs 14.5%, P = .943). The mean dose-length product was 38.2 ± 17.2 mGy-cm and 375.3 ± 115.7 mGy-cm in the low-dose and standard-dose groups ( P < .001). The mean dose-length product was 38.2 ± 17.2 mGy-cm and 375.3 ± 115.7 mGy-cm in the low-dose and standard-dose groups, respectively ( P < .001). The mean effective dose was 0.5 ± 0.2 mSv and 5.3 ± 1.6 mSv in the low-dose and standard-dose groups, respectively ( P < .001). Low-dose CT-guided CNB of lung nodules significantly decreased radiation dose compared with standard-dose CT. The low-dose protocol could provide similar diagnostic accuracy and safety as standard-dose CT-guided CNB for lung nodules.